Silvikultur Intensif Merbau kepada Pengelola Perizinan Berusaha Pemanfaatan Hutan (PBPH) di Papua: Merbau Intensive Silvicultural to Forest Utilization Business Licensing (FUBL) in Papua - Nugroho, Julius D.; Peday, Hans; Hendri, Hendri; Marwa, Jonni; Takim, Mutakim (IGKOJEI: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT  Forest Utilization Business Licensing (FUBL) in Papua has been practicing a silvicultural system for a long time, but the results are still not optimal. Various obstacles in the field such as seed preparation, nursery, planting, and maintenance are still not optimal. Not to mention the erratic fruiting time of Merbau stands and competition from seed-eating pests. This condition can affect the distribution and growth of Merbau stands. One of the reasons is that FUBL has not yet practiced the Merbau Silvicultural Intensive (SILIN) system. Merbau stands are commercial and endemic to Papua, belonging to the class I-II sturdy wood, having hard, sturdy, and durable properties. Currently, merbau is considered a valuable type of wood in the Southeast Asian region and this species is one of the leading species for the Papua region in terms of forest exploitation. This community service activity aims to increase the participants' knowledge, expertise, and understanding of the SILIN Merbau method. This PKM activity was carried out at PT. Wijaya Sentosa in Dusner Village, Kuri Wamesa District, Teluk Wondama Regency on September 5 and 6 2022. The method used in this community service program is community development practice, equipped with a participatory and educative approach with outreach, training, field practice, mentoring, and evaluation. This activity has succeeded in increasing the knowledge, understanding, skills, and independence of training participants, especially FUBL in Papua.  Keywords: FUBL; Intensive silviculture; Merbau stands   ABSTRAK Perizinan Berusaha Pemanfaatan Hutan (PBPH) di Papua telah mempraktikkan sistem silvikultur sejak lama, tetapi hasilnya masih belum optimal. Bermacam hambatan di lapangan seperti persiapan benih, persemaian, penanaman serta pemeliharaan yang masih kurang maksimal. Belum lagi adanya waktu berbuah tegakan Merbau yang tidak menentu dan terdapatnya persaingan dengan hama pemakan biji. keadaan ini bisa mempengaruhi sebaran serta perkembangan tegakan Merbau. Salah satu penyebabnya adalah karena PBPH belum mempraktikkan sistem SILIN Merbau. Tegakan Merbau merupakan kayu komersial serta endemik Papua yang masuk kelas kokoh kayu I- II, mempunyai sifat keras, kokoh serta awet. Saat ini, merbau dianggap sebagai salah satu tipe kayu berharga di wilayah Asia Tenggara serta jenis ini ialah salah satunya jenis unggulan untuk wilayah Papua di dalam hasil pengusahaan hutan. Kegiatan PKM ini bertujuan untuk meningkatkan pengetahuan, keahlian serta pemahaman partisipan terhadap metode SILIN merbau. Kegiatan PKM ini dilaksanakan di PT. Wijaya Sentosa di Kampung Dusner, Distrik Kuri Wamesa, Kabupaten Teluk Wondama pada tanggal 05 dan 06 bulan September tahun 2022. Metode yang digunakan dalam program PKM ini adalah community development practice, dilengkapi pendekatan partisipatif serta edukatif dengan sosialisasi, Pelatihan, Praktik lapangan, pendampingan serta evaluasi. Kegiatan ini telah berhasil meningkatkan pengetahuan, pemahaman, ketrampilan serta kemandirian partisipan pelatihan, kususnya PBPH yang terdapat di Papua. Kata kunci: PBPH; Silvikultur intensif; Tegakan merbau